2008
DOI: 10.1371/journal.pone.0001682
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Arrays Technology (DArT) for Pan-Genomic Evolutionary Studies of Non-Model Organisms

Abstract: BackgroundHigh-throughput tools for pan-genomic study, especially the DNA microarray platform, have sparked a remarkable increase in data production and enabled a shift in the scale at which biological investigation is possible. The use of microarrays to examine evolutionary relationships and processes, however, is predominantly restricted to model or near-model organisms.Methodology/Principal FindingsThis study explores the utility of Diversity Arrays Technology (DArT) in evolutionary studies of non-model org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 37 publications
2
42
0
Order By: Relevance
“…Only one other study has explored the utility of DArT markers for studies of evolution in wild populations (James et al 2008), but that study focused on relationships between populations within two species of cryptogam (a fern, Asplenium viride and a moss, Garovaglia elegans ssp. dietrichiae) rather than inter-specific relationships within a genus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one other study has explored the utility of DArT markers for studies of evolution in wild populations (James et al 2008), but that study focused on relationships between populations within two species of cryptogam (a fern, Asplenium viride and a moss, Garovaglia elegans ssp. dietrichiae) rather than inter-specific relationships within a genus.…”
Section: Introductionmentioning
confidence: 99%
“…dietrichiae) rather than inter-specific relationships within a genus. James et al (2008) found that DArT markers could be highly informative about relationships among populations of cryptogam species.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide marker analysis is currently one of the most powerful tools for determining genetic variation of a crop species and its phylogenetic relationships with wild relatives (1,21). Diversity array technology (DArT) markers are widely accepted as powerful whole-genome profiling markers for phylogenetic and population structure analysis (13,(22)(23)(24)(25). Similar results were obtained in 185 barley accessions using both 1,130 DArT and 1,307 single nucleotide polymorphism (SNP) markers, respectively (13,14).…”
mentioning
confidence: 99%
“…The merits of DArT include a high multiplexing level, simultaneous genotyping of several thousand loci per assay and its simultaneous screening of thousands of polymorphic loci lacking prior genome sequence information; additionally, DArT provides hundreds to tens of thousands of highly reliable markers [120], as well as good genome coverage information [123]. Moreover, sequences of DArT markers are easily accessible compared to AFLPs, making them a preferred technique for non-model species [124]. However, DArT is limited in some applications due to high technicality in preparing genomic representation for the target species, cloning, data management and analysis.…”
Section: Molecular Marker Systemsmentioning
confidence: 99%